A king helps out - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
A King Helps Out is a heartwarming story that illustrates the importance of empathy and community service, as a compassionate king steps down from his throne to assist his subjects in overcoming their challenges and fostering a spirit of unity.